ANALISIS MODEL PEMBIAYAAN INFRASTRUKTUR DI INDONESIA - Oktovianus Yesnat; Putri Bintusy Syathi (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
Abstract Infrastructure is a basic service or a form of hard and soft instruments used to serve and support a network structure in promoting economic and social growth of the community. Meanwhile, infrastructure procurement is a design activity in building and adding conditions as well as implementation and maintenance in order to advance the benefits of infrastructure. In financing infrastructure, the government has a budget shortfall, causing a funding gap. In this study, the aim is to analyze the appropriate model used in financing infrastructure in Indonesia. The method used in this study is a qualitative descriptive method. This method is used to determine the appropriate model used in overcoming the funding gap in infrastructure. The results of the study show that infrastructure financing in Indonesia is very good using the government-business partnership model (PPP), so the government is advised to use PPPs in infrastructure procurement in Indonesia. because in a PPP all accumulated risks can be borne by the government and the private sector and through a PPP the private party can be involved in infrastructure development starting from procurement, financing, to infrastructure maintenance because the private sector has the financial capability and good project management and has qualified human resources and technology. in infrastructure. So that the government is expected to implement regulations regarding the involvement of the private sector in creative financing and local governments are expected to be able to take advantage of regional autonomy.Keywords: Funding Gap, Qualitative Descriptive, Government and Business Entity Cooperation, Creative Financing.